2014
DOI: 10.1088/0031-8949/89/04/044008
|View full text |Cite
|
Sign up to set email alerts
|

Conjoined structures of carbon nanotubes and graphene nanoribbons

Abstract: Hybrid materials built from conjoined structures of graphene nanoribbons (GNRs) and carbon nanotubes (CNTs) have important properties for novel applications. In this communication we have performed a numerical study of these structures and have found two types: (i) CNT and GNR structures formed by van der Waals forces with a distance close to 0.35 nm and (ii) CNT and GNR structures interconnected by short (0.17 nm) and strong chemical bonds. It appears that the latter bonds essentially perturb conjoined carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In previous theoretical research [2] we have found that a benzene molecule can form a chemically bound state with graphene sheet; analogous bound states were found for graphene nanoribbons and carbon nanotubes [3]. Our calculations have shown that the conjoined C 6 rings in the bound CNTs and GNRs are strongly distorted.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In previous theoretical research [2] we have found that a benzene molecule can form a chemically bound state with graphene sheet; analogous bound states were found for graphene nanoribbons and carbon nanotubes [3]. Our calculations have shown that the conjoined C 6 rings in the bound CNTs and GNRs are strongly distorted.…”
Section: Resultssupporting
confidence: 78%
“…Such conjoined structures are numerically found to exist for two graphene sheets [1] and for benzene molecule and graphene [2]. Moreover, as it follows from calculations [3], graphene nanoribbons and carbon nanotubes may also form chemically bound states. In all these cases chemical bonds are established between the adjoined carbon atoms in parallel C 6 rings in a hollow position (here i.e.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, nanocomposites consisting of NTs, GNRs, and other nanomaterials are expected to possess novel electrical and mechanical properties beyond those of the individual components. Therefore, they have attracted much attention in recent years [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the hybrid nanocomposites built from the nanostructure of CNTs and GNRs have also attracted great interest [6][7][8].…”
Section: Introductionmentioning
confidence: 99%